2021
DOI: 10.1097/txd.0000000000001101
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Epidural Analgesia for Postoperative Pain Management in Liver Transplantation: A 10-year Study on 685 Liver Transplant Recipients

Abstract: Background. Thoracic epidural analgesia (TEA) is not widely used for postoperative pain management in liver transplantation due to hepatic coagulopathy-related increased risk of inducing an epidural hematoma. However, an increasing number of patients are transplanted for other indications than the end-stage liver disease and without coagulopathy allowing insertion of an epidural catheter. Methods. This study is a retrospective observational single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…Finally, in our study, all liver recipients were extubated in the OR, showing better results than those presented by Hausken et al, 10 receiving epidural analgesia. Only 32% of the cases were extubated in the OR.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Finally, in our study, all liver recipients were extubated in the OR, showing better results than those presented by Hausken et al, 10 receiving epidural analgesia. Only 32% of the cases were extubated in the OR.…”
Section: Discussioncontrasting
confidence: 45%
“…Epidural analgesia would provide excellent analgesia for these types of surgeries; however, concerns regarding coagulopathy and increased risk of epidural hematoma limit its application. Nonetheless, Hausken et al 10 recently evaluated more than 300 patients who received epidural analgesia for liver transplantation without severe coagulopathy and with good analgesia and no complications. The mean pain scores reported at PODs 0–5 was 1.4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No difference was found in opioid use at discharge or one year. 99 Preoperative or pre-emergence transversus abdominis plane or quadratus lumborum blocks may be applied, and the surgical team can perform local wound infiltration with local anesthetics.…”
Section: Pain Managementmentioning
confidence: 99%
“…reported that patients in a TEA group ( n = 327) had less pain compared to a non‐TEA group ( n = 358), with a mean numeric pain rating scale score of 1.4 versus 1.8 at postoperative days 0–5 ( P = .008). No difference was found in opioid use at discharge or one year 99 . Preoperative or pre‐emergence transversus abdominis plane or quadratus lumborum blocks may be applied, and the surgical team can perform local wound infiltration with local anesthetics.…”
Section: Essentials Of Anesthetic Management Of Ldlt Recipientsmentioning
confidence: 99%